Changing patterns of employee involvement - Gallie, D; Felstead, A; Green, F (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This paper is concerned with the analysis of the trends and determinants of employee involvement in the 1990s. It distinguishes three forms of employee involvement: task discretion (decision-making in the everyday practice of the job), direct participation (the ability to influence local work organisation) and consultative commitment (the ability to express views about wider developments in the organisation). It draws on employee data collected for the 2001 Skills Survey, a national representative sample of people in work. This is compared with equivalent data from national surveys carried out in 1992 and 1997.